2010
DOI: 10.1097/acm.0b013e3181f849dc
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Medical Student Performance on Objective Structured Clinical Exams With Standardized Patients With and Without Disabilities

Abstract: Students performed better when the SP did not have a disability. This suggests that greater emphasis should be placed on teaching appropriate care of patients with a disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…In order to avoid prompting students to give specific responses, the majority of survey questions were open ended; therefore, the fact that so many student respondents were able to identify these subjective factors is significant. Our findings' are similar to those of other published studies (Brown et al, 2010;Jackson, 2007;Larson McNeal et al, 2002;Rose et al, 2011;Thistlethwaite & Ewart, 2003;Tracy & Iacono, 2008) and make a strong case that exposing medical students to encounters with people with disabilities early in their training can improve the students' knowledge, skills, and attitudes ahout disabilities and increase their comfort level in communicating with these patients. Therefore, medical schools should consider introducing curricula to improve their students' knowledge, attitudes, and skills pertaining to people with disabilities.…”
Section: Implications For Educationsupporting
confidence: 94%
“…In order to avoid prompting students to give specific responses, the majority of survey questions were open ended; therefore, the fact that so many student respondents were able to identify these subjective factors is significant. Our findings' are similar to those of other published studies (Brown et al, 2010;Jackson, 2007;Larson McNeal et al, 2002;Rose et al, 2011;Thistlethwaite & Ewart, 2003;Tracy & Iacono, 2008) and make a strong case that exposing medical students to encounters with people with disabilities early in their training can improve the students' knowledge, skills, and attitudes ahout disabilities and increase their comfort level in communicating with these patients. Therefore, medical schools should consider introducing curricula to improve their students' knowledge, attitudes, and skills pertaining to people with disabilities.…”
Section: Implications For Educationsupporting
confidence: 94%
“…Several studies have found that providing specific training to medical students as well as opportunities for them to encounter patients with disabilities yields benefits in terms of improving student's attitudes and comfort level regarding people with disabilities and increasing their knowledge and skills in providing care to these patients (Brown et al 2010;Karl et al 2013;Long-Bellil et al 2011). Few medical schools or residency programs currently offer these kinds of training experiences although this has begun to change (Graham et al 2009;Moroz et al 2010;Symons et al 2009) and research is being conducted to better assess the efficacy of these efforts (Symons et al 2012;Lam et al 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Once at the primary care setting, they may encounter further barriers such as inaccessible examination tables, lack of transfer aides, or accessible weight scales (Mudrick et al 2012;Stillman et al 2014). Furthermore, communication barriers, inadequate time, and provider training may affect the quality of care received by people with disabilities in primary care (Bachman et al 2006;Morrison, George, and Mosqueda 2008;Brown et al 2010;Sharby, Martire, and Iversen 2015).…”
mentioning
confidence: 99%